(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
How can the reuse of memorial traces contribute to adding value to local fashion through thrift stores? Based on this question, how to verify how concepts in the area of social memory, such as memorial traces, can be positive to reveal the value of products and business. The present text, based on theories of social memory, took a sober look at the fashion area, based on “memorial traces”, identified a contribution of the thrift store within the scope of the circular economy. This study does not intend to adhere to the same requirements for the solidarity economy, that is, the sale of second-hand parts to poorer communities. The objective and purpose of this bibliographic research is, based on the proposed conceptual review, to base the knowledge on the themes of social memory, fashion and memory, memorial traces, among others related, in order to bring a further reflection on them within the valuation of the products offered in a thrift store. Therefore, it is also intended to verify how these concepts in the area of social memory can be positive to reveal the value of products and business. For this, we proposed the development of a product, called Communication Diagnosis. This tool is based on the studies and practice in Public Relations.